THE IMPORTANCE OF LINGUISTIC FEATURES IN ENGLISH AND UZBEK (Conference Zone, 2022)
The author of this article looked at the linguistic characteristics, as well as the new construction and creation of compound terms in English and Uzbek. He also tried to understand that word production involves the generation of new lexical units using the language's content and capabilities. This approach is used to continually improve the content of the language dictionary. Compound words are one of the most often utilized word forms nowadays, and they are regarded holistic, concise, and productive. For all languages, compound words are a very important and relevant occurrence. The study of the phenomena of wordformation in terms of synchronous and diachronic periods of language evolution has always been a hot topic, and the English word-formation system has its own linguistic peculiarities. Including compound terms in English necessitates extra care.